Fuel production from microwave assisted pyrolysis of coal with carbon surfaces - Mushtaq, Faisal (Elsevier Ltd, 2016)
In this study, coal solids were subjected to Microwave (MW) pyrolysis conditions. Coconut Activated Carbon (CAC) solids used as a MW absorber was distributed uniformly over coal solids to reduce hotspots. Three process parameters; CAC loading, MW power and N2 flow rate were studies on pyrolysis heating performance. The highest coal-tar yield of 18.59 wt% was obtained with 600 W, 75 wt% CAC loading and 4 Liter per Minute (LPM) of N2 flow rate. This improved coal-tar yield is mainly of the fact that higher MW power and CAC loading produced sustained pyrolysis conditions for longer duration for the complete conversion of pyrolysis solids. The coal-tar was composed mainly of aromatics (naphthalenes, benzenes and xylene) and saturated aliphatics (alkanes and alkenes) hydrocarbons. The gas produced from pyrolysis of coal is mainly of H2 40.23-65.22 vol%.